(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Three fistulated rams with average live weight of 20kg were used as replicates in a completely randomized design (CRD) to study the influence of post-harvest processing methods on chemical composition, In Sacco dry matter degradability (DMD) and organic matter degradability (OMD) of three differently processed Acacia hockii leaf meal. The processed leaf meals (ensiled, T1; sundried, T2 and fresh, T3) were incubated in the rumen of the three rams (3, 6, 12, 24 and 48h incubation time). The processing significantly (p<0.05) reduced the tannin and saponin levels. The highest levels were observed in the fresh leaf meal. There was significant (p<0.05) different in CP contents between the treatments, with T1 having the highest CP content of 15.06%. The CF contents also differed significantly (p<0.05) between the treatments. T3 had the highest CF content (9.23%). T1 had significantly (p<0.05) higher DMD and OMD than T2 and T3. The differences in effective dry matter degradations (EDMD) and effective organic matter degradations (EOMD) were also significant (p<0.05) between the three treatments. It is concluded that the processing methods (ensiling and drying) had positive effect on the chemical composition, DMD and OMD of Acacia (Acacia hockii) leaf meal. It is recommended that ruminant animal farmers, who practice zero grazing, should process Acacia hockii leaf meal before feeding it to their animals for better nutrients availability and utilization.